A break-even analysis and impact analysis of residential solar photovoltaic systems considering state solar incentives - Lee, Minhyun; Hong, Taehoon; Koo, Choongwan; Kim, Chan-Joong (Technological and Economic Development of Economy, 2018)
Despite the steady growth and price reductions of solar photovoltaic (PV) market in the United States (U.S.), the solar PV market still depends on financial support and incentives due to its high initial investment cost. Therefore, this study aimed to conduct a break-even analysis and impact analysis of residential solar PV systems by state in the U.S., focused on state solar incentives. Three indexes (i.e., net present value, profitability index (PI) and payback period) were used to evaluate the investment value of the residential solar PV systems considering state solar incentives. Furthermore, PI increase ratio was used to analyze the impact of state solar incentives on the economic feasibility of the residential solar PV systems in each state. As a result, it was found that 18 of the 51 target cities have reached the break-even point and seven of the 51 target cities showed great improvement of the economic feasibility of solar PV systems in the U.S. due to excellent state solar incentives. The results of this study can help policy makers to evaluate and compare the economic impacts of the residential solar PV systems by state in the U.S.First published online: 09 Feb 2017